Analisis Kelayakan Penggantian Nozzle Soot Blower pada PT. PJB UP Paiton Unit 1 dan 2 - Cecilia Intan Wijayanti; Wahyudi Sutopo (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2017)
High electricity demand requires power companies to maintain the efficiency of every generation process. One factor affecting the efficiency of the production system is the reliability of the machine. Nozzle is a sparepart of the tool used to clean slaging on the wall of the boiler is Soot Blower . Soot Blower's current condition consumes steam nearly 400,000 kg/year from the ideal condition 332,000 kg/year. The high consumption of steam causes the high cost of coal and low efficiency Soot Blower. One alternative that can be offered is to replace the Nozzle with a new type that has a lower pressure that is Nozzle Gemini. The new alternative compared based on operational analysis that see comparison from preference matrix weight and financial analysis that see comparison on 10 year projection by Net Present Value(NPV), IRR and PP analysis. And it is known on both analysis of Gemini Nozzle usage is feasible to be applied.